2022
DOI: 10.1186/s12888-021-03676-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of minimally invasive facial cosmetic surgery in Chinese college students

Abstract: Background Minimally invasive facial cosmetic surgery (MIFCS) is becoming more and more popular and acceptable in Chinese young people, and it influences people in many aspects. However, there is little research on the associations between MIFCS and psychopathology in Chinese college students. The purpose of this study was to identify the prevalence of MIFCS and its associated factors among Chinese college students. Methods A cross-sectional design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…This result is consistent with a Chinese study from 2019, which reported a mean score of 37.1 (SD 8.0) among university students [ 34 ]. However, it is a little lower than another Chinese study and a Russian study, which showed mean SDS scores for university students of 44.4 (SD 9.9) and 47.8 (SD 10), respectively [ 35 , 36 ]. In contrast, the mean GAD-7 scores reported in previous studies (including a Chinese, an Ethiopian, and an American study) were more than 6 in university students [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 67%
“…This result is consistent with a Chinese study from 2019, which reported a mean score of 37.1 (SD 8.0) among university students [ 34 ]. However, it is a little lower than another Chinese study and a Russian study, which showed mean SDS scores for university students of 44.4 (SD 9.9) and 47.8 (SD 10), respectively [ 35 , 36 ]. In contrast, the mean GAD-7 scores reported in previous studies (including a Chinese, an Ethiopian, and an American study) were more than 6 in university students [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 67%
“…51 A Chinese study with 63.3% of women sample revealed that the reasons for finding a mate were chosen by 11 or 5.0% of the sample. 52 Another study that took samples from five countries in East Asia with female proportions between 54.3% to 70.8% revealed that 9.2% or 136 respondents performed aesthetic procedures because they were suggested by a https://doi.org/10.2147/CCID.S398685…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, four out of seven studies in Asia, involving samples from East Asia and West Asia, indicated explicitly that men were the reason women chose laser procedures. [50][51][52][53] It is also interesting to note that the only study in Australia also shows direct male influence, in the form of partners in close relationships, as a source of motivation for choosing cosmetic procedures. 54…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…There was evidence that women performed better in the recognition of minor modifications in facial skin than men ( Samson et al, 2010b ). This difference may be explained by the fact that the main consumers of cosmetic and facial beauty treatments are women ( Jin et al, 2022 ; Mohammed et al, 2022 ), making them to be more sensitive to facial skin conditions. Male and female judgments of male and female faces were mostly consistent in this study.…”
Section: Experiments 2: Perceiving Facial Attractiveness Changementioning
confidence: 99%